Loss estimation model for a mobile microcell based on a mobile application (2019)
There is the possibility of measuring the reception power by means of a mobile device to determine the coverage area of a mobile cell, with experimental type research in the field is carried out the installation of an application on mobile devices. The methodology is made up of the following stages: measurement campaigns, equipment configuration, connectivity tests, data capture and processing, mathematical formulation of an empirical model and statistical analysis of results on outdoor environments.